Efficiency analysis of SAT solvers in logic locking applications - Liu, Zhiyuan (Nanyang Technological University, 2024)
As globalization affects integrated circuit (IC) design, logic locking has emerged as an important protective strategy against numerous security threats. Since the introduction of the SAT attack method, the reliability of logic locking has been questioned. This development has spurred further research into SAT attacks and their effects on logic lock defenses. However, the literature currently lacks a comparative analysis of the efficiency of different SAT solvers.